3D-Printed Surgical Steel Curettes for the Treatment of Perianal Fistula. (June 2021) - Pérez Lara, Francisco Javier; Diaz de Tuesta Revilla, Ignacio; Moya Donoso, Francisco Javier; Hernández González, Jose Manuel; Prieto-Puga Arjona, Tatiana
Need. The diversity of approaches proposed for the treatment of complex perianal fistulas reflects the fact that no method has yet been shown to be fully satisfactory. We believe the successful treatment of this condition is directly proportional to the amount of fibrous tissue that can be removed. Technical solution. We use a kit of small curettes, of different thicknesses and sizes, incorporating spicules that enable the physician to remove fibrous tissue from the fistula tract. The small size and varying thicknesses of the curettes enable them to mould to the curves of the fistula tract and to remove tissue by deroofing from the shallowest to the deepest layers, thus excising the entire fibrous tract. Our hospital has recently incorporated into clinical practice a new model of 3D-printed surgical steel curette, flanked by 2 lateral rings through which the suture is threaded. The central part of the curette contains radially graduated discs, the tips of which perform the debriding action, removing the fibrous tissue from the tract. Proof of concept. By using these curettes in conjunction with our standard technique (plugging the tract with platelet-rich fibrin), we have improved the success rate from 67% to 88%. Next steps. We have contacted several companies with a view to marketing this product. Conclusion. The results obtained are significantly better than those offered by the techniques in current use for the treatment of complex fistulas, without prejudice to outcomes such as anal continence and morbidity and mortality.